Effects of daily ingestion of sodium bicarbonate on acid-base status and anaerobic performance during an altitude sojourn at high altitude: a randomized controlled trial - Mirjam Limmer; Markus de Marées; Petra Platen (Taylor & Francis Group, 2020)
Background The present study investigated the effects of chronic sodium bicarbonate (NaHCO3) ingestion on a single bout of high-intensity exercise and on acid-base balance during 7-day high-altitude exposure. Methods Ten recreationally active subjects participated in a pre-test at sea level and a 7-day hiking tour in the Swiss Alps up to 4554 m above sea level. Subjects received either a daily dose of 0.3 g/kg NaHCO3 solution (n = 5) or water as a placebo (n = 5) for 7 days. Anaerobic high-intensity exercise performance was assessed using the portable tethered sprint running (PTSR) test under normoxic and hypoxic conditions (3585 m). PTSR tests assessed overall peak force, mean force, and fatigue index. Blood lactate levels and blood gas parameters were assessed pre- and post-PTSR. Urinary pH and blood gas parameters were further analyzed daily at rest in early morning samples under normoxic and hypoxic conditions. Results There were no significant differences between the bicarbonate and control group in any of the PTSR-related parameters. However, urinary pH (p = 0.003, ηp2 = 0.458), early morning blood bicarbonate concentration (p < 0.001, ηp2 = 0.457) and base excess (p = 0.002, ηp2 = 0.436) were significantly higher in the bicarbonate group compared with the control group under hypoxic conditions. Conclusions These results indicate that oral NaHCO3 ingestion does not ameliorate the hypoxia-induced impairment in anaerobic, high-intensity exercise performance, represented by PTSR-related test parameters, under hypobaric, hypoxic conditions, but the maximal performance measurements may have been negatively affected by other factors, such as poor implementation of PTSR test instructions, pre-acclimatization, the time course of hypoxia-induced renal [HCO3 −] compensation, changes in the concentrations of intra- and extracellular ions others than [H+] and [HCO3 −], or gastrointestinal disturbances caused by NaHCO3 ingestion. However, chronic NaHCO3 ingestion improves blood bicarbonate concentration and base excess at altitude, which partially represent the blood buffering capacity.